Application of Constructability Concepts in the Industrialised Building System for the Malaysian Construction Industry - Jelodar, Mostafa Babaeian (2009)
Constructability is generally reducing the problems of construction by incorporating the construction knowledge into the design of a construction project. The Malaysian construction industry is attempting to promote and use Industrialized Building systems (IBS) for better construction practice with more effectiveness and efficiency, but in terms of constructability and research into the application of constructability concepts for IBS little work has been done. In fact the Malaysian construction industry is still not applying the concepts of constructability in totality and there is lack of constructability research in Malaysia. In this research the application status of constructability concepts which have been previously defined for Malaysia are examined and assessed within the Malaysian IBS industry. The ease of constructability application of IBS and conventional building methods are investigated and finally the concepts that are not being applied up to their potential level in IBS construction and resemble possible problems in the process of application are identified. A survey is used to obtain the essential data needed for the research from the active IBS industry participants of Malaysia. It was found that the IBS contractors are applying constructability more than the designers and suppliers and also the early constructability concepts gained a higher application score than other concepts. Using information technology and the innovative concepts of the field operation phase were the most difficult concepts to apply and generally the application of constructability concepts in IBS construction is easier compared to the conventional building systems according to the IBS industry participants.